Detection of blaOXA-48 and mcr-1 Genes in Escherichia coli Isolates from Pigeon (Columba livia) in Algeria - Lotfi Loucif; Widad Chelaghma; Esma Bendjama; Zineb Cherak; Meriem Khellaf; Asma Khemri; Jean-Marc Rolain (Microorganisms, 2022)
The emergence and spread of β-lactams and colistin-resistant Escherichia coli in birds deserve a special concern worldwide. This study aimed to investigate the presence of β-lactams and colistin-resistant Escherichia coli strains isolated from the faeces of urban and rural pigeons in Batna, Algeria, and to characterise their molecular traits of resistance. Between March and April 2019, a total of 276 faecal droppings samples were collected in Batna, Algeria. Samples were subjected to selective isolation of β-lactams and colistin-resistant Escherichia coli. The representative colonies were then identified using Matrix-Assisted Laser Desorption-Ionization Time-of-Flight Mass Spectrometry. Antimicrobial susceptibility testing was performed using the disc diffusion method. β-lactamases, as well as mcr genes, were screened for by PCR and confirmed by sequencing. Genetic relatedness of the mcr-positive E. coli strains was determined using multi-locus sequence typing analysis. Transferability features of carbapenemase genes were assessed by conjugation experiments. Overall, thirty-five E. coli isolates were obtained only from urban pigeon samples. All carbapenem-resistant isolates harboured the blaOXA-48 gene as the only carbapenemase gene detected (n = 11), while blaESBL genes were detected in eighteen isolates. Out of the thirty-five isolates, four E. coli isolates were positive for the mcr-1 gene. The obtained mcr-1 positive E. coli isolates belonged to four STs, including ST1485, ST224, ST46, and a new ST. This study is the first to report the isolation of E. coli strains carrying the mcr-1 gene from pigeon faeces in Algeria and also the first to report the detection of blaOXA-48-positive E. coli in pigeons. Close surveillance is, therefore, urgently needed to monitor the dissemination of blaOXA-48 and mcr-1 producing E. coli strains in wildlife.